Everybody's a Victim? Global Terror, Well-Being and Political Attitudes - Alpaslan Akay; Olivier Bargain; Ahmed Elsayed (Institute of Labor Economics (IZA), 2018)
Terror has become a global issue. Terror acts perpetuated by religious, nationalist or political groups around the globe can propagate distress rapidly through different channels and possibly change political attitudes. This paper suggests the first evaluation of the impact of global terror on human welfare. We combine panel datasets for Australia, Germany, Russia, Switzerland, the UK and the US. Individual well-being information for 750,000 individual x year observations, recorded on precise dates, is matched with daily information on the 70,000 terror events that took place worldwide during 1994–2013. High-frequency data and quasi-random terror shocks of varying intensity provide the conditions for robust inference, while external validity is guaranteed by the use of large representative samples. We find a significantly negative effect of global terror on well-being, with a money-metric cost of around 6%–17% of national income. Among diffusion channels, stock markets and economic anticipations play a minimal role, while traditional media filter the most salient events. The effect is greatly modulated by the physical, genetic or cultural proximity to the terror regions/victims. For a subset of countries, we also show that global terror has significantly increased the intention to vote for conservative parties. Heterogeneity analyses point to the mediating effect of risk perception: individuals who exhibit stronger emotional responses to terror – possibly more exposed to potential threats – are also more likely to experience a conservative shift.
Keywords: C99; D60; D72; D74; I31; 330; global terror; subjective well-being; media; political attitudes